Assessing the Feasibility and Effectiveness of Screening for Indoor Tanning in the Primary Care Setting: A Report of Preliminary Findings - Allison B. Robbins, MD; Mimi R. Borrelli, MBBS, PhD; Fatima N. Mirza, MD, MPH; Nicole A. Negbenebor, MD; Helena M. Kuhn, MD; Tiffany J. Libby, MD (Elsevier, 2024)
Introduction: Indoor tanning is a major modifiable risk factor in the development of both melanoma and nonmelanoma skin cancers. Investigation of behavior-altering interventions is an area of active research. As with other preventive measures, screening of high-risk populations can be an important aspect of a multimodality public health intervention. This study sought to further the limited understanding of indoor tanning screening practices in the primary care setting. Methods: Physicians practicing within the scope of primary care in the northeast were surveyed in 2022 on practice patterns around the frequency of indoor tanning screening, barriers encountered with implementing screening, and actions taken with a positive screen. Research methodology adhered to the Joanna Briggs Institute critical appraisal checklist. Results: Of 26 primary care physicians, only 7.7% routinely screened for indoor tanning. Barriers identified included time limitations (76.9%) and prioritization of other health concerns (96.2%). All primary care physicians (100%) reacted to reports of indoor tanning with an intervention, most commonly counseling on the risks of indoor tanning (92.6%). Conclusions: This data suggest that screening for indoor tanning use could be improved. The authors recommend the incorporation of a standardized screening question regarding indoor tanning in intake forms.